Invitro fertilization outcome in triggering with GnRH agonist, Hcg or combination of GnRH agonist and Hcg - Alamtaj Samsami; Sara Davoodi; Shaghayegh Moradi Alamdarloo; Tahere Poordast; Zahra Shiravani; Azade Morshedzadeh (Mashhad University of Medical Sciences, 2020)
Introduction: Human chorionic gonadotropin for the final maturation of eggs in the In-vitro fertilization cycle was associated with the possibility of a negative effect on endometrial acceptance, fetal quality and ovarian hyper stimulation syndrome. Replacing it with a gonadotropin-releasing hormone agonist to trigger final ovulation is expected to reduce these effects. Therefore, this study was performed with aim to evaluate the outcome of triggering in in vitro fertilization with antagonist protocol by gonadotropin-releasing hormone agonist, human chorionic gonadotropin simultaneously with human gonadotropin-releasing hormone agonist and human chorionic gonadotropin.  Methods: In this randomized clinical trial study conducted in 2015 and 2016, women were divided into three random groups after preparing the follicles for triggering and ovum retrieval. One group received 0.2 mg of dipherline, the second group received 10,000 units of human chorionic gonadotropin and the other group received 0.2 mg of dipherline along with 1500 units of human chorionic gonadotropin. The number and quality of eggs and embryos were the outcomes of the study. Data were analyzed by SPSS software (version 17) and Leven tests and one-way analysis of variance. P < 0.05 was considered statistically significant.  Results: The number of retrieved oocytes in the group receiving gonadotropin-releasing agonist was significantly higher than the other groups (p = 0.001). More embryos were produced in the gonadotropin-releasing hormone agonist group compared to the other two groups (p = 0.009). However, the number of high quality embryos produced in the groups was similar. Conclusion: The onset of final oocyte maturation with gonadotropin-releasing hormone agonist significantly increases the number of retrieved oocytes and obtained embryos. However, dual stimulation using low-dose human chorionic gonadotropin (IU1500) and gonadotropin-releasing hormone agonist did not alter quality of embryo compared to the standard dose of human chorionic gonadotropin (IU10000).